Migration and Urbanity in Rural Areas. Developments in the German-Luxembourg Border Region - Boesen, Elisabeth; Schnuer, Gregor; Wille, Christian (Geographien der Grenzen. Räume - Ordnungen - Verflechtungen, 2020)
Abstract: „Studies on the connection between migration and urbanity are usually concerned with conditions and developments in cities. The presence of ‘urbanity’ in rural space is the topic of the present contribution. It will be discussed using the example of residential migration in the Greater Region SaarLorLux. The massive influx of residential migrants from Luxembourg into the border regions of the neighbouring countries is a relatively recent phenomenon, the main cause of which lies in the developments in the real-estate market in the Grand Duchy of Luxembourg. This phenomenon is of special interest for the topic of migration in rural areas in two regards: because of the important demographic changes produced by the residential migrants in individual border villages and because of the complex composition of the group of residential migrants, which is extremely differentiated regarding the dimension rural—urban. Central to the article is the question, whether urban attitudes and practices become visible in German border villages, and, if so, how the migratory movement from Luxembourg influences this ‘rural urbanity’. Furthermore, taking the everyday practices of the residential migrants as starting point, it asks in how far the dichotomy urbanity—rurality presents a conceptual approach for the examination of individual and structural integration processes.“
Keywords: Ländliche Entwicklung; Ländlicher Raum; Migration; Stadt

Living in the house of the hangman. Post-war relations between Jews and non-Jews in the German-Dutch border region - Demant, Froukje (Juden und Nichtjuden nach der Shoah. Begegnungen in Deutschland, 2019)
Keywords: Emsland; Grafschaft Bentheim; Juden; Judenverfolgung; Judenvernichtung; Ländlicher Raum; Münsterland (West); Rückkehr; Überlebender

Safeguarding services in health provision and health care in rural border areas – An investigation using the example of the Greater Region - Mangels, Kirsten; Riethmüller, Robert (Cross-Border Territorial Development – Challenges and Opportunities, 2018)
Keywords: Bevölkerungsentwicklung; Grenzüberschreitende Kooperation; Ländlicher Raum; Medizinische Versorgung

De lakenfabriek Scheibler, Ronstorff, Rahlenbeck te Dalem (1774–1890). Een voorbeeld van industrialisatie op het platteland - Leboutte, René (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 1979)
„R. Leboutte, medewerker van het Musée de Fer et de l'Acier te Luik, geeft een overzicht van de geschiedenis van een middelgroot textielbedrijf te Dalem. Deze studie is daarom zo belangrijk, omdat Dalem een der hoofdplaatsen van de landen van Overmaze is geweest en tot aan het laatste kwart van de 18e eeuw onder Noord-Nederlands bestuur heeft gestaan. Desondanks is aan de historie van deze stad in de Nederlands-Limburgse historiografie nooit veel aandacht besteed. Hoewel dit verzuim door het hier gepubliceerde artikel uiteraard niet geheel wordt goedgemaakt, is het toch verheugend dat aan de hand van het gebeuren in Dalem de samenhang tussen de bedrijvigheid in Eifel, Ardennen en Zuid-Limburg kan worden verduidelijkt. De stichters van de hier bestudeerde onderneming, de familie Scheibler, had destijds industriële belangen in Monschau, Eupen, Eijsden en Dalem, een gebied dat eens samenhang vertoonde en thans door de 19e eeuwse grensafbakening in drie staten terecht gekomen is.“
Keywords: Dalhem; Eijsden; Eupen; Ländlicher Raum; Monschau; Textilindustrie; Wirtschaftsbeziehungen